Role of Ce 4f States in the Electronic Structure and Photoelectrochemical Activity of Brannerite CeTi2O6–X - Hachemi, Cyril; Debbichi, Mourad; Galipaud, Jules; Mesbah, Adel; Aizac, Yoann; Badawi, Michael; Geantet, Christophe; Prévot, Mathieu S.; Cardenas, Luis (Chemistry of materials, 2025)
Cerium has been proposed as an attractive element in photoconversion systems, but the role of the Ce3+/Ce4+ redox couple in light-driven processes remains a subject of debate due to the localized nature of Ce 4f electrons. Moreover, in state-of-the-art TiO2 photoabsorbers, Ce doping generally introduces various defects, complicating the interpretation of the contribution of cerium. In this study, we address this question by synthesizing brannerite CeTi2O6 thin films and powders and treating them with H2 to form isostructural CeTi2O6–x phases, in which Ce4+ cations are selectively reduced to Ce3+. The reduction introduces deep intragap Ce 4f states, which greatly enhance visible light absorption for the material. However, when studied as photoelectrodes, CeTi2O6–x thin films exhibit decreased activity compared to the pristine material under one sun illumination. We investigate this behavior through a combination of spectroscopic techniques and theoretical modeling, and we build a detailed electronic band diagram for CeTi2O6 and its reduced counterparts. We show that, apart from the appearance of intragap Ce 4f states, the overall band structure remains largely unchanged across different reduction levels. Moreover, density functional theory calculations suggest that the exciton binding energy increased after reduction, leading to inefficient charge separation, which counteracts the benefits of enhanced visible-light absorption. Overall, this study proposes a robust and comprehensive methodology to describe the band structure of photoabsorbers and to decipher the influence of intragap states on their light absorption and conversion properties, well beyond the CeTi2O6 system.